Patient‐reported experiences of mealtime care and food access in acute and rehabilitation hospital settings: a cross‐sectional survey. Issue 4 (25th January 2021) - Kozica‐Olenski, S.; Treleaven, E.; Hewitt, M.; McRae, P.; Young, A.; Walsh, Z.; Mudge, A.
Abstract: Background: Nutrition and mealtime interventions can improve nutritional intake amongst hospital inpatients; however, patient‐reported experience is rarely considered in their development and evaluation. The present study aimed to measure patient‐reported food and mealtime experience to evaluate and inform continuous quality improvement of hospital nutrition care. Methods: A cross‐sectional survey with inpatients in seven acute care and rehabilitation wards was conducted. A 27‐item validated questionnaire measured five domains of patient experience: food choices, organisational barriers, feeling hungry, physical barriers to eating and food quality. Responses were summarised descriptively and compared between settings (acute versus rehabilitation), patient demographics (age, gender) and time in hospital. Results: Responses from 143 participants (mean age 67 years, 57% male, 28% rehabilitation, median 6 days into hospitalisation) showed that 10% or fewer respondents reported difficulties with food choices, feeling hungry or food quality. The most common difficulties were opening packets (36%), insufficient menu information provided (29%), being interrupted by staff when eating (28%), being disturbed when eating (27%), being in an uncomfortable position when eating (24%) and difficulty reaching food (21%). There were no significant differences in domain patterns by sex, age group or time in hospital. Organisational barriers were reported less frequently amongst rehabilitation participants compared to acute care ( P = 0.01). Conclusions: This survey highlights areas of positive patient‐reported experience with nutrition care and suggests that local improvement efforts should focus on physical assistance needs and organisational barriers, especially in acute care wards. The questionnaire may be useful for informing and evaluating systematic nutrition care improvements. Abstract : The present study aimed to measure patient‐reported food and mealtime experience to evaluate and inform continuous quality improvement of hospital nutrition care. The most common difficulties experienced by patients at meals times included opening packets, insufficient menu information provided, interruptions by staff when eating and eating in an uncomfortable position. This survey highlights areas of positive patient‐reported experience with nutrition care and suggests that local improvement efforts should focus on physical assistance needs and organisational barriers, especially in acute care wards.